SYSTEMATIC LITERATUR REVIEW: KEMAMPUAN BERPIKIR KRITIS DENGAN MENGGUNAKAN PENDEKATAN PENDIDIKAN MATEMATIKA REALISITIK INDONESIA (PMRI) - Mulbasari, Anggria Septiani; Putri, Ratu Ilma Indra; Zulkardi, Zulkardi; Aisyah, Nyimas (LP4MK STKIP PGRI Lubuklinggau, 2023)
This study aims to conduct a literature review related to critical thinking skills using the PMRI approach. The method used is a systematic literature review (SLR). The data explored are articles related to Critical Thinking Ability Using the PMRI Approach for the period 2010-2021. From a number of articles that were traced from sinta 1 - 4, 8 articles were found that matched critical thinking skills using the PMRI approach. Based on the results analyzed, it can be concluded that using the PMRI approach can improve critical thinking skills, students are very enthusiastic in learning using the PMRI approach. Creative and innovative teachers using the PMRI approach can make learning mathematics fun, more interesting, less boring and liked by students. In addition, the application of learning with the PMRI approach, as well as the classroom atmosphere can improve critical thinking skills, and also have a direct impact on improving students' critical thinking skills and better student characteristics.